2019
DOI: 10.12669/pjms.35.1.95
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammatory markers following Ramadan Fasting

Abstract: Objectives: The aim of present study was to investigate the effect of fasting during Ramadan on plasma adiponectin and TNF-α levels. Methods: This is a cross sectional study, conducted at Federal Urdu University of Arts, Science & Technology (FUUAST), Karachi, comprising a total of 55 (50%) females and 55 (50%) males whose ages ranged between 20 and 40 years, and fasted during Ramadan (June-July 2014) were enrolled in the study. Subjects were separated into normal weight, overweight and obese males a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
(25 reference statements)
1
23
0
5
Order By: Relevance
“…The presence of the MetS has also been associated with lower plasma adiponectin levels (117) , indicating adipose tissue dysfunction and a two-to four-times increased risk for developing CVD and type 2 diabetes (118) . Similarly, several reports have indicated RDIF was associated with variable increments in adiponectin levels in fasting people (119)(120)(121) . Recently, we found that RDIF was associated with significant reduction in visceral fat surface area (measured by MRI) in fifty-seven overweight/obese participants, concomitant with significant reductions proinflammatory cytokines (IL-6 and TNF-α), and a significant increase in the anti-inflammatory cytokine IL-10 (122) .…”
Section: Discussionmentioning
confidence: 73%
“…The presence of the MetS has also been associated with lower plasma adiponectin levels (117) , indicating adipose tissue dysfunction and a two-to four-times increased risk for developing CVD and type 2 diabetes (118) . Similarly, several reports have indicated RDIF was associated with variable increments in adiponectin levels in fasting people (119)(120)(121) . Recently, we found that RDIF was associated with significant reduction in visceral fat surface area (measured by MRI) in fifty-seven overweight/obese participants, concomitant with significant reductions proinflammatory cytokines (IL-6 and TNF-α), and a significant increase in the anti-inflammatory cytokine IL-10 (122) .…”
Section: Discussionmentioning
confidence: 73%
“…In our study, adiponectin was significantly decreased by Ramadan fasting in Type 2 DM, FDRs, and healthy control groups, which is in agreement with studies reporting a significant decrease in adiponectin level during the fasting period in healthy controls [ 22 , 45 ] and in overweight/obese individuals [ 46 ], and a decrease in the expression of adiponectin in patients with Type 2 DM [ 47 ]. Other studies, however, reported that adiponectin either increased in healthy controls that have risk factors for Type 2 DM [ 48 , 49 ] or did not change in healthy individuals [ 7 , 42 ]. The observed decrease in adiponectin can be explained by the altered sleeping/feeding pattern during Ramadan, as well as by the previously reported changes in cortisol secretion [ 9 ], where the adiponectin concentrations exhibit ultradian pulsatility, as well as diurnal variation, with a significant nocturnal decline, reaching minimum values in the early morning [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, changes in the body cause the stem cells to regenerate new cells in the immune system ( 20 , 41 ). The promising results of studies have shown that inflammatory cytokines (e.g., IL-1β, IL-6, and TNF-α), oxidative stress markers and C-reactive protein (CRP) might be reduced by Ramadan fasting ( 20 , 42 , 43 ).…”
Section: Ramadan Fasting May Affect Immune Functionmentioning
confidence: 99%